Access 2007 VBA bible for data-centric Microsoft Office applications - Feddema, Helen Bell.; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2007)
"In this all-new, comprehensive guide by well-known Access expert Helen Feddema, you'll learn to write Visual Basic code that automates Access database tasks, creates standalone scripts, extracts and merges data, and allows you to put together powerful solutions. Whether you're a beginner or a power user, this is the book you need to succeed with Access 2007"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Microsoft Access; Database management; Microsoft Visual Basic for applications; Microsoft Office; Electronic books